2001
DOI: 10.1051/lait:2001136
|View full text |Cite
|
Sign up to set email alerts
|

Propionibacteria and facultatively heterofermentative lactobacilli weakly contribute to secondary proteolysis of Emmental cheese

Abstract: -Proteolysis is a major event during cheese ripening. In Emmental cheese, the contribution of plasmin and thermophilic lactic starters to proteolysis has been well established. Our aim was to assess the contribution of each ripening flora to secondary proteolysis. With this aim, we used the aqueous phase (or juice) of Emmental cheese as a culture medium, which contains the enzymes released by thermophilic starters. Crude juice (containing all cheese flora) and cell-free juice either inoculated with two propion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
22
0
2

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 34 publications
5
22
0
2
Order By: Relevance
“…In contrast, although it possesses diverse intracellular peptidases, P. freudenreichii has a limited role in secondary proteolysis, compared to starter and non-starter lactic acid bacteria (NSLAB), because it does not lyse in cheese [66].…”
Section: Dairy Starters For Swiss-type Cheeses and Other Productsmentioning
confidence: 99%
“…In contrast, although it possesses diverse intracellular peptidases, P. freudenreichii has a limited role in secondary proteolysis, compared to starter and non-starter lactic acid bacteria (NSLAB), because it does not lyse in cheese [66].…”
Section: Dairy Starters For Swiss-type Cheeses and Other Productsmentioning
confidence: 99%
“…Langsrud et al (21,22) observed a correlation between autolysis of propionibacteria in milk and production of free proline, and Østlie et al (31) confirmed this correlation for broth media. Gagnaire et al (13) showed that strains of P. freudenreichii did not contribute to proteolysis in an aqueous phase in Emmental cheese and that propionibacteria were not significantly involved in the production of proline. Few peptidases from P. freudenreichii were also found in Emmental cheese by a proteomic approach (12).…”
Section: Resultsmentioning
confidence: 99%
“…The NSLAB in Swiss-type cheese are mainly composed of FHL that begin growth at the beginning of ripening [35] and eventually reach~10 8 cfu·g −1 [109]. In a study by Demarigny et al [21], L. paracasei, L. plantarum, L. rhamnosus and L. brevis were all detected in Swiss-type cheese, but as the cheese ripened L. paracasei began to dominate the NSLAB flora.…”
Section: Fhlmentioning
confidence: 96%
“…Berdagué et al [6] and Grappin et al [43] related split intensity to higher levels of secondary proteolysis as measured nitrogen levels soluble in phosphotungstic acid. In Swiss-type cheese, plasmin and the proteinases and peptidases from starter, non-starter and secondary starter [34,35] are the principal proteolytic agents [25,93]. The activity of proteolytic enzymes in cheese is influenced by a w , copper content, water content, lactic acid concentration, pH, storage temperature and time [105].…”
Section: Influence Of Manufacturementioning
confidence: 99%
See 1 more Smart Citation